Perception of quality of life of a group of individuals subjected to bariatric surgery - Salazar-Maya, Ángela María; Hoyos Duque, Teresa Nury; Bojanini-Acevedo, Lucas (Investigación y Educación en Enfermería, 2014)
Objective. The study sought to identify the state of health and quality of life of post-bariatric surgery patients. Methodology. This was a cross-sectional study conducted in 2012 with the participation of 338 individuals attending the private practice of a bariatric surgeon from Medellín (Colombia). With prior signed informed consent, the survey was filled out by each patient. The information gathered was sociodemographic in nature along with the World Health Organization’s Quality of Life Brief Questionnaire (WHOQoL-Bref). Results. It was found that 82.2% were women and mean age was 41±12 years. Gastric bypass was practiced on 79.6% of the cases. Mean weight before surgery was 106.3±17.5 Kg and after surgery it was 73.2±13.4 Kg. Nine of every 10 participants classified their quality of life and state of health between extremely well and quite well. Quality of life was better in men, in those younger than 40 years of age, in those from socio-economic levels 4 to 6, and in those with educational level above the secondary (high school). Conclusion. As a consequence of the important and rapid weight loss occurring during the first months after surgery, most of the participants perceived having a good quality of life and were satisfied with their health status. For nursing, it is a challenge to implement educational programs and projects, bearing in mind the sociocultural diversity of the individuals and communities, through interdisciplinary and inter-sector work, which contributes to the well-being of obese individuals subjected to bariatric surgery and their families.